Gas Adsorption in Metal-Organic Frameworks : Fundamentals and Applications - Glover, T. Grant; Mu, Bin; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
This text discusses the synthesis, characterization, and application of metal-organic frameworks (MOFs) for the purpose of adsorbing gases. It provides details on the fundamentals of thermodynamics, mass transfer, and diffusion that are commonly required when evaluating MOF materials for gas separation and storage applications and includes a discussion of molecular simulation tools needed to examine gas adsorption in MOFs. Additionally, the work presents techniques that can be used to characterize MOFs after gas adsorption has occurred and provides guidance on the water stability of these materials. Lastly, applications of MOFs are considered with a discussion of how to measure the gas storage capacity of MOFs, a discussion of how to screen MOFs to for filtration applications, and a discussion of the use of MOFs to perform industrial separations, such as olefin/paraffin separations. Throughout the work, fundamental information, such as a discussion on the calculation of MOF surface area and description of adsorption phenomena in packed-beds, is balanced with a discussion of the results from research literature.
Safety and Acknowledgements. List of Contributors. MetalOrganic Frameworks and Reticular Chemistry. Synthesis and Characterization of MetalOrganic Frameworks. Thermodynamics of Adsorption. Mass Transfer in MOFs. Packed Bed Wave Theory. Simulation of Crystalline Nanoporous Materials and the Computation of Adsorption/Diffusion Properties. Characterization Techniques for the Analysis of MetalOrganic Frameworks During and after Adsorption. Water Stability of MetalOrganic Frameworks . Gas storage in Water Stability of MetalOrganic Frameworks. Toxic Gas Adsorption & Reaction in Metal-Organic Frameworks. Potential Industrial Applications of MetalOrganic Frameworks for Gas Separations. Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: Organometallic compounds; Crystallography; SCIENCE / Chemistry / General; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Electronic books